2021
DOI: 10.3389/fphys.2021.577698
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in Ground Reaction Forces During Turns by Elite Slalom Alpine Skiers Are Not Related to Asymmetries in Muscular Strength

Abstract: The ground reaction forces (GRF) associated with competitive alpine skiing, which are relatively large, might be asymmetric during left and right turns due to asymmetries in the strength of the legs and torso and the present investigation was designed to evaluate this possibility. While skiing a symmetrical, 20-gate slalom course, the asymmetries of 9 elite alpine skiers were calculated on the basis of measurements provided by inertial motion units (IMU), a Global Navigation Satellite System and pressure insol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The current results also mirror the demands faced by alpine skiers, where effective balance and motor control are required to cope with course setting, terrain variety, and snow conditions ( Gilgien et al, 2018 ). Therefore, in agreement with present results and previous findings, we can speculate that the better dynamic balance of high-ranking skiers could be a factor that can exert considerable influence on the successful performance of alpine ski racers ( Ogrin et al, 2021 ). Our results contrast with those of Noè and Paillard who reported similar static and sport-specific balance performances in skiers at regional and national levels ( Noé and Paillard, 2005 ), and support previous research on the use of sport-specific dynamic balance tests to ensure the proper selectivity among athletes ( Asseman et al, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current results also mirror the demands faced by alpine skiers, where effective balance and motor control are required to cope with course setting, terrain variety, and snow conditions ( Gilgien et al, 2018 ). Therefore, in agreement with present results and previous findings, we can speculate that the better dynamic balance of high-ranking skiers could be a factor that can exert considerable influence on the successful performance of alpine ski racers ( Ogrin et al, 2021 ). Our results contrast with those of Noè and Paillard who reported similar static and sport-specific balance performances in skiers at regional and national levels ( Noé and Paillard, 2005 ), and support previous research on the use of sport-specific dynamic balance tests to ensure the proper selectivity among athletes ( Asseman et al, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings indicated that the dominant and non-dominant limbs equally contributed to the management of the SST ( Table 4 ; Figure 4 ) independently from the skiers’ ranking level. However, the high-ranking group expressed the best balance performance ( Table 2 ) despite the magnitude of ground reaction forces while turning on-snow is different for the inner and the outer leg ( Ogrin et al, 2021 ). Again, we can speculate that high-ranking skiers adopted more effective control strategies to overcome the constraints at the ankle joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings could therefore be of potential interest for practitioners working with freeski populations. However, unilateral strength measurement values recorded in the laboratory may not be correlated to the ground reaction force kinetics in the sport (Ogrin et al, 2021 ). Further research is required to determine a detailed physiological and neuromuscular profile of academy to elite freeski athletes.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the number of phases into which a turn should be divided. There are authors who have divided the turn into two [4][5][6][7], three [2,3,[8][9][10] or four phases [11,12]. However, most studies agree on a fundamental division on two phases within the turn: the initiation (INI) phase, described as the motion between turns where lateral forces are non-existent, and…”
Section: Introductionmentioning
confidence: 99%